REMAP RT (Reading Concept Map Reciprocal Teaching) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Mar’atus Sholihah; Siti Zubaidah; Susriyati Mahanal (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Critical thinking is one of the skills that students must have to solve a problems in everyday life appropriately. Critical thinking skills have not been empowered well in learning process. That’s skills can be empowered with specific learning models, that was Remap RT (Reading Concept Map Reciprocal Teaching) learning model. The research objective to empower critical thinking skills of first grade students of high schools on the course from Biology by applying Remap RT. The type of research was quasi-experimental research with Pretest-Posttest Nonequivalent Control Group Design. The sample was the students of X MIA 2 and X MIA 4 in SMAN 2 Batu. Student’s critical thinking skills were measured using an essay test that scored by rubric of critical thinking skills integrated with an essay test. Data were analysis using Anacova test. The results showed Remap RT learning model influence on students' critical thinking skills. Students that learned with Remap RT learning model have critical thinking skills increased by 147.49%, while students that learned with conventional learning-based scientific approaches to increase critical thinking skills by 111.02%.  Based on the results, we can conclude that Remap RT learning model has a higher potential in improving students' critical thinking skills than conventional learning-based scientific approach, because of the Remap RT syntax have potential to develop critical thinking skills.Keywords:      Critical thinking skills, Remap RT